2′-fucosyllactose alone or combined with resistant starch increases circulating short-chain fatty acids in lean men and men with prediabetes and obesity - Canfora, Emanuel E.; Vliex, Lars M. M.; Wang, Taojun; Nauta, Arjen; Bouwman, Freek G.; Holst, Jens J.; Venema, Koen; Zoetendal, Erwin G.; Blaak, Ellen E. (Frontiers in Nutrition, 2023)
Background Infusion of short-chain fatty acids (SCFA) to the distal colon beneficially affects human substrate and energy metabolism. Here, we hypothesized that the combination of 2′-fucosyllactose (2′-FL) with resistant starch (RS) increases distal colonic SCFA production and improves metabolic parameters. Methods In this randomized, crossover study, 10 lean (BMI 20–24.9 kg/m2) and nine men with prediabetes and overweight/obesity (BMI 25–35 kg/m2) were supplemented with either 2′-FL, 2′-FL+RS, or placebo one day before a clinical investigation day (CID). During the CID, blood samples were collected after a overnight fast and after intake of a liquid high-fat mixed meal to determine plasma SCFA (primary outcomes). Secondary outcomes were fasting and postprandial plasma insulin, glucose, free fatty acid (FFA), glucagon-like peptide-1, and peptide YY concentrations. In addition, fecal SCFA and microbiota composition, energy expenditure and substrate oxidation (indirect calorimetry), and breath hydrogen excretion were determined. Results In lean men, supplementation with 2′-FL increased postprandial plasma acetate (P = 0.017) and fasting H2 excretion (P = 0.041) compared to placebo. Postprandial plasma butyrate concentration increased after 2′-FL and 2′-FL+RS as compared to placebo (P < 0.05) in lean men and men with prediabetes and overweight/obesity. Additionally, 2′-FL+RS decreased fasting and postprandial plasma FFA concentrations compared to placebo (P < 0.05) in lean men. Conclusion Supplementation of 2′-FL with/without RS the day before investigation increased systemic butyrate concentrations in lean men as well as in men with prediabetes and obesity, while acetate only increased in lean men. The combination of 2′-FL with RS showed a putatively beneficial metabolic effect by lowering plasma FFA in lean men, indicating a phenotype-specific effect. Clinical trial registration nr. NCT04795804.